Crystal structure of aqua(1,10-phenanthroline)bis(2-thiophenecarboxylato) copper(II), Cu(H2O)(C12H8N2)(C4H3SCOO)2 - Feng D.-M. (Zeitschrift für Kristallographie - New Crystal Structures, 2005)
C22H16CuN2O5S2, monoclinic, P121/c1 (no. 14), a = 8.4228(4) Å, b = 19.7169(7) Å, c = 12.4746(5) Å, β = 91.041(2)°, V = 2071.3 Å3, Z = 4, Rgt(F) = 0.067, wRref(F2) = 0.199, T = 295 K.